2020
DOI: 10.1101/cshperspect.a038349
|View full text |Cite
|
Sign up to set email alerts
|

H7N9 Influenza Virus in China

Abstract: In early 2013, human infections caused by a novel H7N9 avian influenza virus (AIV) were first reported in China; these infections caused severe disease and death. The virus was initially low pathogenic to poultry, enabling it to spread widely in different provinces, especially in live poultry markets. Importantly, the H7N9 low pathogenic AIVs (LPAIVs) evolved into highly pathogenic AIVs (HPAIVs) in the beginning of 2017, causing a greater threat to human health and devastating losses to the poultry industry. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 65 publications
(56 citation statements)
references
References 144 publications
(235 reference statements)
1
35
0
1
Order By: Relevance
“…H5N1 and H7N9 AIV are enzootic in domestic poultry in China (8,(52)(53)(54). Rational use of vaccination can be an important measure for prevention and control of these two subtypes.…”
Section: Discussionmentioning
confidence: 99%
“…H5N1 and H7N9 AIV are enzootic in domestic poultry in China (8,(52)(53)(54). Rational use of vaccination can be an important measure for prevention and control of these two subtypes.…”
Section: Discussionmentioning
confidence: 99%
“…Large scale surveillance performed before and after the H5/H7 inactivated vaccine application indicated that the vaccination program dramatically reduced the prevalence of H7N9 virus in poultry [ 7 ]. More importantly, the vaccination of chickens successfully prevented human infections with H7N9 virus as indicated by the fact that there were 766 human cases reported between October 1, 2016, and September 30, 2017, but only three and one human case over the same time period of the following two years [ 13 , 14 ], and no human case has been detected since March 2019 [ 1 , 15 ] ( S1 Fig ).…”
Section: Introductionmentioning
confidence: 99%
“…The first human infection with H5N1 AIV occurred in Hong Kong in 1997 [3], and between 2003 and 2020, 861 human infection cases were reported, of which 455 were fatal [4]. The H7N9 low pathogenic AIVs identified in 2013 and the subsequently mutated H7N9 highly pathogenic AIVs in 2017 [5][6][7][8] led to 1568 human infections, including 615 fatal cases [9]. Therefore, continued efforts to elucidate the factors and mechanisms underlying the pathogenesis and transmission of IAVs remain critical for the development of novel anti-influenza therapies.…”
Section: Introductionmentioning
confidence: 99%